2017
DOI: 10.1001/jama.2017.3091
|View full text |Cite
|
Sign up to set email alerts
|

Types and Distribution of Payments From Industry to Physicians in 2015

Abstract: According to data from 2015 Open Payments reports, 48% of physicians were reported to have received a total of $2.4 billion in industry-related payments, primarily general payments, with a higher likelihood and higher value of payments to physicians in surgical vs primary care specialties and to male vs female physicians.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

14
228
8

Year Published

2017
2017
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 200 publications
(281 citation statements)
references
References 34 publications
(84 reference statements)
14
228
8
Order By: Relevance
“…They found that male physicians, oncologists (relative to nononcologists), solo practitioners, and those in high Medicare spending regions were more likely to accept transfers. Using 2015 OPD, Tringale et al examined conditional transfers using regression analysis. They found that males and those in high Medicare spending regions accepted more transfers and that solo practitioners accepted less.…”
Section: Existing Literaturementioning
confidence: 99%
“…They found that male physicians, oncologists (relative to nononcologists), solo practitioners, and those in high Medicare spending regions were more likely to accept transfers. Using 2015 OPD, Tringale et al examined conditional transfers using regression analysis. They found that males and those in high Medicare spending regions accepted more transfers and that solo practitioners accepted less.…”
Section: Existing Literaturementioning
confidence: 99%
“…We used a recent observational retrospective stud focusing on industry payments to physicians by specialty for comparison data. 16 Simple descriptive statistics were used for data analysis. Total payments of each type (total general payments, direct total research payments, and indirect associated research funding) averaging complete 2014 to 2016 data are detailed in Table 1 below.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…We hypothesized that physician journal editors would have a non-negligible rate of financial COI though lower than the estimated rate among clinicians in the field, previously established using the same data source. 16 …”
Section: Introductionmentioning
confidence: 99%
“…According to the Physician Payments Sunshine Act, a component of the 2010 Affordable Care Act, all pharmaceutical and manufacturers of medical devices must publicly report payments to physicians and teaching hospitals that are at least $10 in value on the Centers for Medicare and Medicaid Services website . According to this database, called Open Payments, the median value of general payments made to emergency medicine physicians by industry in 2015 was $50 with an interquartile range of $18 to $125 …”
mentioning
confidence: 99%